تغیرِ زمانہ اور تغیرِ حال کے سبب ظنی احکام اور فتاوی میں تبدیلی کے اصول و ضوابط اور عصر حاضر میں ان کی تطبیق (Al-Qamar, 2023)
Issuing a verdict on a current situation and event in the light of Allah’s commands is called a fatwā. In Sharī‘ah, there is room for change in the fatwā due to the changes in the circumstances, which is clearly indicated by various definitive texts of the Qur’ān and Sunnah. The change in the fatwā means that the reasons for which a certain legal ruling was acted upon have changed, so the fatwā has also changed. That is, something that the early jurists had declared unlawful by their own reasoning, but later jurists declared it permissible due to the change of circumstances. There are countless examples in front of us in which the previous ruling of something has been abandoned and a new ruling has been issued. And this change has been going on from the era of the Prophet to the present era. There are four reasons on the basis of which change can be made in the fatwā: ratio-legis, custom, necessity, and blocking the means. It has always been the opinion of Muslim jurists that a woman cannot perform Ḥajj without a maḥram (a male family companion with whom marriage is prohibited), however, the scholars of the present era have given this fatwā that if a woman’s husband or maḥram gives her permission to go on the journey of Ḥajj without a maḥram, then it is permissible. The reason for this change in the fatwā is that the cause of the prohibition of traveling without a maḥram, i.e., the fear of corruption, is no longer found. A woman can safely perform the obligatory Ḥajj by choosing modern means of travel and secure accommodation without a maḥram. Those fatwās that are based on the Qur’ān, Sunnah and consensus of the Ummah, there is no room for change in them. However, only those fatwās that are based on analogy, reasoning, custom and habit, etc., can be changed according to the changing circumstances, which is in accordance with the Sharī‘ah. Therefore, it is the duty of the scholars and intellectuals to examine the new issues arising in their era in the light of these four cases of change in the fatwā and issue such a fatwā that makes things easier.
Keywords: fatwā; ratio-legis; custom; blocking the means; change of time; change of fatwā